Female dolphins use individual vocal labels to track coercive males - Alice Bouchard; Simon J. Allen; Pernille M. Sørensen; Michael Krützen; Svenja M. Marfurt; Richard C. Connor; Stephanie L. King (Proceedings of the National Academy of Sciences, 2026)
Animals rely on identity signaling to navigate social relationships, assess potential mates, and avoid costly interactions. While species- and group-level recognition signals can provide fitness advantages by preventing inbreeding depression and hybridization, our understanding of the role that individual identity signals can play in mate choice is notably lacking. In species with coercive mating systems, females must carefully evaluate male behavior to minimize risks while also maximizing reproductive success, yet the mechanisms that enable them to monitor and respond to male behavior remain poorly understood. Male Indo-Pacific bottlenose dolphins form multilevel alliances to compete for access to reproductive females, with important consequences for how females negotiate their relationships with males. In this study, we investigated how females assess males by conducting 34 sound playbacks to 17 females and using drone-mounted video to analyze their behavioral responses to individual male identity signals. We combined these experiments with long-term behavioral data to examine how female reproductive state, sociability, and interaction history shaped their responses. Females who were reproductively available showed a significantly stronger aversive response to the identity signals of males who coerced females at higher rates, suggesting that females track male behavior across time and use individual vocal labels to guide reproductive decision-making based on their experience of individual male behavior. This capacity suggests that females integrate social knowledge about individual males to strategically manage intersexual relationships and mate choice.